Pendampingan Komunikasi pada Praktik Posyandu Remaja dalam Mewujudkan New Zero Stunting - Fitria, Nadia Salsa; Nurhadi, Zikri Fachrul (Penerbit Goodwood, 2025)
Purpose: This service aims to educate teenagers about the importance of preventing stunting from an early age, as well as providing free health checks through the practice of Posyandu Remaja. Methodology/approach: The methods used in this service include lectures, discussions, and health checks, which are divided into several stages: observation, preparation, implementation, monitoring, and evaluation. Results/findings: The results of this service showed significant success, with an ‘increase in participants' understanding, as seen in the post-test results. Conclusion: Adolescent communication support through the Adolescent Posyandu effectively increases understanding of nutrition, anemia, and stunting prevention. Sustainability, collaboration, and innovation are needed to achieve zero stunting. Limitations: This assistance is a pioneer; therefore, sustainability is needed for further services. In the future, this service must be supported by health workers who are more competent and reach many other adolescents. Contribution: Based on the results of this service, it is recommended to implement Posyandu Remaja on an ongoing basis, update educational materials according to the latest health developments, and ’carry ’out regular ’monitoring and ’evaluation to measure the effectiveness of the ‘program. With the implementation of these steps, it is expected that communication assistance activities in Posyandu Remaja practices will ’be more effective and have a positive ’impact on stunting prevention in Sumedang Regency.